A KONSEP PROFIL PELAJAR RAHMATAN LIL'ALAMIN (P2 RA) (ANALISIS DAMPAKNYA TERHADAP PENGALAMAN BERAGAMA PESERTA DIDIK) - Sari, Sri Wulan; Ahmad Darlis; Fauzul Azmi Purba; Gadis Ayuni Putri (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2024)
This research discusses the concept of the rahmatan lil'alamin profile (analysis of its impact on students' religious experiences). The type of research used in this paper is descriptive qualitative. Then for data collection techniques using library research which is very related to this discussion. The results of this research show that it is necessary to know what the concept of Rahmatan Lil'alamin's student profile actually looks like so that it can be used as a role model for students who study it. And the impact that Rahmatan Lil'alamin has on students' religious experiences is that students no longer commit violations at school because they know the sanctions they will receive. And students who understand the impact of rahmatan lil'alamin will continue to take care of themselves and control themselves to be on the right path. Keywords : Student Concept, Rahmatan Lil'alamin, Religious Experience